PENINGKATAN AKTIVITAS BELAJAR PAK MELALUI MODEL PEMBELAJARAN PROBLEM SOLVING PADA SISWA KELAS IX-B SMPK BETHEL JAKARTA-PUSAT - Lisa Sri Rejeki Rodearni; Johni Hardori (Edukasi : Jurnal Pendidikan Agama Kristen, 2020)
The purpose of this study was to get an overview, to increase PAK learning activities through problem-solving learning models in PAK learning for class IX-B students of SMP K Bethel Jakarta-Pusat. This research was conducted at SMP K Bethel Jakarta-Pusat, with the subjects studied were students of class IX-B. The method used is classroom action research which consists of two cycles. In the first cycle, learning was carried out by applying a problem-solving learning model accompanied by observation sheets of student learning activities. Whereas in cycle II learning was also carried out by applying a problem-solving learning model accompanied by observation sheets of student learning activities and a list of questions. Each cycle consists of four stages of research, namely planning, implementing actions, observing, and reflecting. The research data were analyzed using comparative descriptive followed by reflection. Comparative descriptive is done by comparing data on initial conditions, cycle 1 and cycle 2, for student learning activities. The results of this study indicate that the application of the problem-solving learning model can improve the learning activities of class IX-B students of SMP K Bethel Jakarta-Pusat. It is proven that the percentage of students in PAK learning activities increases from the initial condition 0.58% to 70.5% in the first cycle and to 100% in the second cycle or in the final condition, an increase of 99.42% from the initial condition.